Description of a New Type of the Genus Pseudonapaeus (Gastropoda, Pulmonata, Enidae) from Fergana Valley (International Journal of Psychosocial Rehabilitation, 2020)
Descriptions of a new species are presented, which differ: The shell is bullet-shaped, the upper parts are conical with a rounded apex, the mouth is almost whole, the V-shaped folds are very short, and there is only one longitudinal roller.